2022
DOI: 10.3389/fnhum.2022.907716
|View full text |Cite
|
Sign up to set email alerts
|

Centromedian thalamic neuromodulation for the treatment of idiopathic generalized epilepsy

Abstract: Idiopathic generalized epilepsy (IGE) is a common type of epilepsy and despite an increase in the number of available anti-seizure medications, approximately 20–30% of people with IGE continue to experience seizures despite adequate medication trials. Unlike focal epilepsy, resective surgery is not a viable treatment option for IGE; however, neuromodulation may be an effective surgical treatment for people with IGE. Thalamic stimulation through deep brain stimulation (DBS) and responsive neurostimulation (RNS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Based on the results of randomized controlled trials and larger clinical series, the best evidence exists for DBS of the anterior thalamic nucleus. Studies of DBS to CMT have reported significant reductions in seizures following implantation and stimulation, [42][43][44][45] although randomized trials are required. 13 Some researchers suggest more efficient deep brain stimulation of ANT for focal seizures, wider use of CMT for generalized seizures, and hippocampal DBS for temporal lobe seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of randomized controlled trials and larger clinical series, the best evidence exists for DBS of the anterior thalamic nucleus. Studies of DBS to CMT have reported significant reductions in seizures following implantation and stimulation, [42][43][44][45] although randomized trials are required. 13 Some researchers suggest more efficient deep brain stimulation of ANT for focal seizures, wider use of CMT for generalized seizures, and hippocampal DBS for temporal lobe seizures.…”
Section: Discussionmentioning
confidence: 99%
“…3,19 The use of neuromodulation is being studied and expanded for the treatment of some generalized epilepsy syndromes, with some promising early data in idiopathic generalized epilepsies. 20 A patient with drug-resistant EEM underwent responsive neurostimulation targeting the centromedian/ ventrolateral nucleus of the thalamus, which reduced daily absence seizures from 60 to ≤10. 21 Further work is necessary to understand the use of neuromodulation in this syndrome and the optimal target.…”
Section: Discussionmentioning
confidence: 99%
“…However, fenfluramine was found to be effective in a study of 10 patients with sunflower syndrome, which has been classified as a subgroup of EEM with prominent photic stimulation 3,19 . The use of neuromodulation is being studied and expanded for the treatment of some generalized epilepsy syndromes, with some promising early data in idiopathic generalized epilepsies 20 . A patient with drug‐resistant EEM underwent responsive neurostimulation targeting the centromedian/ventrolateral nucleus of the thalamus, which reduced daily absence seizures from 60 to ≤10 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Given clinical limitations, the final number of thalamic electrodes ranged from 1-5 to monitor 1-6 thalamic nuclei. We did not implant in the centromedian thalamic nucleus in this series because its location was not within the trajectory of most other targets, and because it may be more involved with non-temporal lobe epilepsies(Velasco et al ., 1987; Fisher et al ., 1992; Velasco et al ., 2006; Zillgitt et al ., 2022)…”
Section: Methodsmentioning
confidence: 99%
“…Given clinical limitations, the final number of thalamic electrodes ranged from 1-5 to monitor 1-6 thalamic nuclei. We did not implant in the centromedian thalamic nucleus in this series because its location was not within the trajectory of most other targets, and because it may be more involved with non-temporal lobe epilepsies (Velasco et al, 1987;Fisher et al, 1992;Velasco et al, 2006;Zillgitt et al, 2022) Electrode trajectory planning: High resolution T1, fast gray matter acquisition T1 inversion recovery (FGATIR), and T1 post-contrast imaging were used for planning. All patients required frontal and temporal opercular and/or insular coverage.…”
Section: Patient Selectionmentioning
confidence: 99%